Peran Penyuluh Agama dalam Program Desa Binaan Keluarga Sakinah Di Desa Dlingo - Nurkholis Nurkholis; Istifianah Istifianah; Ahmad Syafii Rahman (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2020)
Religious counsellor are officials under the Ministry of Religion who are in charge, responsible and have full authority to carry out religious guidance and development education activities through religious language. The Religious Instructor is one of the parties in the implementation of the Sakinah Family Assistance Village Program (SFAF). Based on their duties and authority as civil servants, this research was held at the same time to find the factors that support and hinder the implementation of the program. This qualitative study concludes that they support the implementation of the DBKS not moving much more than according to their duties and functions as religious extension agents. However, the main thing that hinders the social conditions in religious knowledge, and the problem of early marriage becomes an obstacle even though the support for coordination between the parties involved in the program in Dlingo has been well established. So this program can be continued because of its positive impact in motivating people to have religion.